Recent Land Use and Land Cover Change Dynamics in the Gran Chaco Americano - Banchero, Santiago; De Abelleyra, Diego; Veron, Santiago Ramón; Mosciaro, Maria Jesus; Arévalos, Fabiana; Volante, Jose Norberto (International Society of Photogrammetry and Remote Sensing, 2023)
Trabajo presentado al 2020 IEEE Latin American GRSS & ISPRS Remote Sensing Conference (LAGIRS 2020), 22–26 March 2020, Santiago, Chile.